Straw return rearranges soil pore structure improving soil moisture memory in a maize field experiment under rainfed conditions - Junkai Wang; Caixia Sun; Yulan Zhang; Junyao Xiao; Yueping Ma; Jialin Jiang; Zhengde Jiang; Lili Zhang (Agricultural Water Management)
Straw return is commonly used to improve soil fertility and quality, thereby contributing to improved crop production; however, the influence of different straw management on soil moisture variation, its response to precipitation, and soil pore properties remains largely inadequate, let alone the relationships between these factors. To fill this knowledge gap, the temporal dynamics of soil moisture were monitored during the maize growing season from 2022 to 2023 in a fixed-site field experiment on straw return, including straw removal (CK), straw direct incorporation (SD) and straw-derived biochar incorporation (BC), in Northeast China. In contrast to CK, BC was observed to have a significant impact on soil moisture, increasing the monthly average of September by 30.3 % and the annual average by 5.90 % in 2022 (P < 0.05). In addition, SD significantly increased the average for June by 28.5 % (P < 0.05) and exhibited a more pronounced linear correlation between soil moisture and rainfall amount with the greatest slope (y = 0.2061x + 0.0026, R² = 0.3098). The results indicated that the soil water storage capacity was enhanced when straw was returned, with a more effective impact in BC in 2022 but in SD in 2023, partially attributing to the discrepancies in precipitation quantity, intensity, and frequency between the two years. Furthermore, BC significantly reduced the dissipated precipitation fraction and enhanced the soil water memory in both 2022 (P < 0.05) and 2023 (P < 0.01), based on the evaluation of the capacity of soil to retain water. The results of X-ray computed tomography (CT) scanning showed that straw return resulted in the reconstruction of a relatively intricate pore network, which was characterized by an increase in porosity and macropore number in SD, an increase in pore circularity, a reduction in pore diameter and maccropore number in BC, which was associated with soil layer depth. It is concluded that the improvement of soil water and pore properties, as evidenced by an enhanced soil moisture memory and an increased porosity, contributed to the enhancement of soil nutrients under straw return conditions. This study provides valuable insights for selecting a suitable mode of straw return, thereby facilitating the effective utilization of straw and water resources in agricultural systems, particularly in arid regions.